Women’s empowerment projects also need to engage men for a real change: A review of literature - Gartaula, Hom Nath; Atreya, Kishor; Sapkota, Anisha; Mukhopadhyay, Prama; Chadha, Deepali; Puskur, Ranjitha (CGIAR Initiative on Gender Equality, 2024)
This study examined women’s empowerment in agriculture and rural development projects that have used the project-level women’s empowerment in agriculture index (pro-WEAI) framework for impact assessment. The study categorized project impacts as negative, no impact, positive but non-significant (p>0.05), and positive and significant (p<0.05). The findings revealed mixed outcomes: Many projects improved women’s empowerment in the areas of income autonomy, group membership, asset ownership, and financial access. However, negative impacts were noted in the areas of work balance and attitudes towards intimate partner violence, often due to male backlash, lack of direct asset transfers, and unaddressed gender norms. Projects that actively engaged men and women, provided productive assets, and offered skill-building training showed significant positive impacts on women’s agency. While some progress is evident, achieving transformative change requires tackling entrenched social norms and inequalities. The study suggests the adoption of gender-transformative approaches and integrating socio-technical innovations to holistically support gender equality and sustainable empowerment outcomes in future development projects.